What Determines Effectiveness of Renewable Energy Standards? General Equilibrium Analytical Model and Empirical Analysis - Don Fullerton; Chi L. Ta (Center for Economic Studies and ifo Institute (CESifo), 2022)
Our new analytical general equilibrium model is used to study effects of tightening state Renewable Portfolio Standards (RPS) on electricity price, CO2 emissions, fossil fuel electricity generation, and two kinds of renewable generation. We show how those outcomes depend on key state characteristics such as endowments of potential intermittent and non-intermittent ("dispatchable") renewable sources and the degree of intermittency. Our three extensions investigate key assumptions. We prove theorems and derive empirical hypotheses about what state characteristics makes RPS programs more effective. Using U.S. state-level data from 1990 to 2015, we find the data are consistent with these hypotheses.
Keywords: H21; H23; Q58; 330; renewable portfolio standards; emissions; electricity generation; renewable power